A normative perspective on the linguistic intergroup bias: How intragroup approval of ingroup members who use the linguistic intergroup bias perpetuates explicit intergroup bias. (9th September 2019) - Assilaméhou‐Kunz, Yvette; Postmes, Tom; Testé, Benoit
Abstract: The present research examined from a normative perspective how intragroup normative processes regulate the consequences of the linguistic intergroup bias (LIB). Results of three studies supported our hypothesis that intragroup approval of an ingroup member who uses the LIB plays a key role in perpetuating pro‐ingroup bias. In Study 1, ingroup members who used pro‐ingroup (vs. pro‐outgroup) LIB elicited more intragroup approval and this effect was mediated by the perception of the speaker as being biased in favor of the ingroup. In Studies 2 and 3, intragroup approval (vs. disapproval) of an ingroup member who used the LIB enhanced the expression of pro‐ingroup bias. By providing the first demonstration of how the LIB relates to intragroup normative processes, our studies highlight a new path by which the LIB helps perpetuate intergroup bias.